POLITIK PEMBERLAKUAN SYARI`AT ISLAM DI ACEH DAN KELANTAN (1993-2014) - Khamami Zada (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2015)
The application of Islamic rules in Aceh and Kelantan is also related to the political power. There is a significant difference about political treatment on the application of Islamic law in Aceh and Kelantan. In Aceh, the central government (Indonesia) thinks that it is needed to apply jinâyah law in Aceh as a strategy to solve conflicts. This political rule has been applied in the republic of Indonesia since the leadership of Habibie, Abdurrahman Wahid, Megawati Soekarno Putri to Susilo Bambang Yudhoyono. The main factor that influences the Indonesian political government rule is the central conflict with the Acehnese in the leadership of Soeharto presidential to the Helsinski Agreement 2005. Some vertical conflicts happened between the central government and the Acehnese were solved by giving special autonomy in applying the Islamic rules. Not only family law and economic law which are given autonomy to be applied in Aceh, but also the autonomy to apply jinâyah Law. In Kelantan, Federal government (Malaysia) did not have political wish to apply Jinayah Law in Kelantan since the leadership of Mahathir Muhammad, Abdullah Badawi to Najib Razak. Moreover the federal government made the issue of the application of jinâyah law as the political commodity to get the political sympathy from the people, who are the partner of non Moslem voters in the national ranks and some Moslem voters who are not affiliated with PAS. This political needs factor is kept by the Federal Government to respond the Kelantan’s government wish to apply Islamic rules.Copyright (c) 2015 by Al-Ihkam. All right reserved DOI : 10.19105/al-ihkam.v10i1.588